Analysis of Sediment Grain Size of the Beaches of Aeng Village, Takalar Regency and Padongko Beach, Barru Regency - Umar, Hasdinar; Rachman, Taufiqur; Rahman, Sabaruddin; Paotonan, Chairul; Baeda, Achmad Yasir; Taufiqurrahman, Taufiqurrahman; Alkhaer, Ilham (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2020)
Beach is an area that is physically subject to change. This change is caused by natural processes and human activities. Physical changes that generally occur on the beach are erosion and sedimentation. The dynamic processes that occur at the beach are the result of a combination of various forces at work on the beach, which include the force of waves, currents, sedimentary movements, wind and so on. To analyze sediment transport in coastal areas, one of the main things that need to be known is the characteristics of coastal sediments. The study was carried out on beaches prone to erosion and sedimentation, the location of sample data research at several points taken in the area around the Aeng Takalar Village Beach and Padongko Barru Beach. The analysis carried out is the analysis of the distribution of sediment grains to determine the characteristics of existing sediments on the beach. The results showed that the sizes of the sediment samples on the beach in Aeng Village, Takalar District were a mixture of fine sand and medium sand which had a diameter of 0.125 mm - 0.5 mm and the size of the sediment grains on the Padongko beach. Kabru was a mixture of fine sand and medium sand which has a diameter of 0.125 - 0.5 mm.